Bibliometric and visualized analysis of the relationship between rheumatoid arthritis and periodontitis-related bacteria using CiteSpace software - Lin, Tianqiong; Xu, Zehong; Chen, Jiali; Wang, Xiaoyu; Li, Qiaoping; Ye, Biying; Hu, Chaoyan (Frontiers in Microbiology, 2025)
BackgroundRheumatoid arthritis (RA) is a chronic systemic autoimmune disease of unknown etiology. Recent studies have indicated a potential relationship between the oral microbiome and the onset and progression of RA. However, research trends in this area have not been comprehensively examined. The aim of this study was to conduct a bibliometric analysis of the relationship between RA and the oral microbiome from January 1, 1995, to January 10, 2024, to elucidate the research landscape, including hot topics and emerging trends.MethodsWe extracted literature related to RA and the oral microbiome from the Web of Science database. Utilizing CiteSpace software, we analyzed publications, countries, institutions, authors, and keywords through a visual knowledge graph to assess research hotspots and trends.ResultsIn total, 833 articles were identified, revealing a consistent increase in the number of annual publications in this field over the study period. The United States has emerged as the leading country in terms of publication volume, with Harvard University being the most prolific institution. Among the authors, Jan Potempa has the highest number of publications. Keyword analysis indicated that current research hotspots concerning the relationship between RA and the oral microbiome primarily focus on Porphyromonas gingivalis, periodontitis, inflammation, expression, and peptidylarginine deiminase. Investigating the mechanisms by which oral and intestinal microorganisms influence RA, as well as developing intervention strategies targeting these microbiotas, is anticipated to be a significant future research direction.ConclusionThis study characterized the trends in the literature regarding the relationship between RA and the oral microbiome, providing valuable insights for scholars pursuing further research.